Carrera de Administración de Empresas de la UEB receptó examen complexivo - García García, Mariana (2023)
Since Thursday, July 27, 17 students enrolled in the Business Administration Career of the Faculty of Administrative Sciences, Business Management and IT in Group “C” of the degree, took the theoretical exam as part of the complex exam modality, which It was taken from 9:00 a.m. to 11:00 a.m. in the Accounting laboratories